The Australasian dingo archetype: de novo chromosome-length genome assembly, DNA methylome, and cranial morphology. (28th March 2023) - Ballard, J William O; Field, Matt A; Edwards, Richard J; Wilson, Laura A B; Koungoulos, Loukas G; Rosen, Benjamin D; Chernoff, Barry; Dudchenko, Olga; Omer, Arina; Keilwagen, Jens; Skvortsova, Ksenia; Bogdanovic, Ozren; et al.
Abstract: Background: One difficulty in testing the hypothesis that the Australasian dingo is a functional intermediate between wild wolves and domesticated breed dogs is that there is no reference specimen. Here we link a high-quality de novo long-read chromosomal assembly with epigenetic footprints and morphology to describe the Alpine dingo female named Cooinda. It was critical to establish an Alpine dingo reference because this ecotype occurs throughout coastal eastern Australia where the first drawings and descriptions were completed. Findings: We generated a high-quality chromosome-level reference genome assembly (Canfam_ADS) using a combination of Pacific Bioscience, Oxford Nanopore, 10X Genomics, Bionano, and Hi-C technologies. Compared to the previously published Desert dingo assembly, there are large structural rearrangements on chromosomes 11, 16, 25, and 26. Phylogenetic analyses of chromosomal data from Cooinda the Alpine dingo and 9 previously published de novo canine assemblies show dingoes are monophyletic and basal to domestic dogs. Network analyses show that the mitochondrial DNA genome clusters within the southeastern lineage, as expected for an Alpine dingo. Comparison of regulatory regions identified 2 differentially methylated regions within glucagon receptor GCGR and histone deacetylase HDAC4 genes that are unmethylated in the Alpine dingo genome but hypermethylated in the Desert dingo. Morphologic data, comprising geometric morphometric assessment of cranial morphology, place dingo Cooinda within population-level variation for Alpine dingoes. Magnetic resonance imaging of brain tissue shows she had a larger cranial capacity than a similar-sized domestic dog. Conclusions: These combined data support the hypothesis that the dingo Cooinda fits the spectrum of genetic and morphologic characteristics typical of the Alpine ecotype. We propose that she be considered the archetype specimen for future research investigating the evolutionary history, morphology, physiology, and ecology of dingoes. The female has been taxidermically prepared and is now at the Australian Museum, Sydney.